2021
DOI: 10.1007/s40520-021-01791-5
|View full text |Cite
|
Sign up to set email alerts
|

The patterns and burden of multimorbidity in geriatric patients with prolonged use of addictive medications

Abstract: Background Multimorbidity and prolonged use of addictive medications are prevalent among older patients, and known to increase the risk of adverse drug events. Yet, the relationship between these two entities has remained understudied. Aims This study explored the association between multimorbidity burden and prolonged use of addictive medications in geriatric patients, adjusted for clinically important covariates. Furthermore, we identified comorbidity pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…With increasing age, item inter-correlations, especially for the “inner resilience and coherence subscale” (subscale 1), dissolved. Reasons for lower correlations are the prospect of a shorter remaining lifespan, combined with simultaneously experiencing multimorbidity and functional limitations, which can lead to the use of polypharmacy [ 4 ] and prolonged addictive medication [ 5 ]. In a recent study, polypharmacy has been found to be strongly associated with disease burden in geriatric individuals [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With increasing age, item inter-correlations, especially for the “inner resilience and coherence subscale” (subscale 1), dissolved. Reasons for lower correlations are the prospect of a shorter remaining lifespan, combined with simultaneously experiencing multimorbidity and functional limitations, which can lead to the use of polypharmacy [ 4 ] and prolonged addictive medication [ 5 ]. In a recent study, polypharmacy has been found to be strongly associated with disease burden in geriatric individuals [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for lower correlations are the prospect of a shorter remaining lifespan, combined with simultaneously experiencing multimorbidity and functional limitations, which can lead to the use of polypharmacy [ 4 ] and prolonged addictive medication [ 5 ]. In a recent study, polypharmacy has been found to be strongly associated with disease burden in geriatric individuals [ 5 ]. It is likely that the prospect of not being able to restore health negatively reflects on coherence and less stable ICS scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comorbidity was not an independent predictor of mortality, which is in contrast to other research [ 5 , 7 ]. This discrepancy might be related to prolonged CNSD use being associated with comorbidity, [ 28 ], but with uncertain causal direction of the relationship. Furthermore, both CNSDs and comorbidity influences cognitive function in older patients [ 30 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between somatic comorbidity, cognitive function and prolonged use of CNSDs is difficult to determine. This is especially related to the link between comorbidity and CNSD use [ 28 ], which both affects cognitive function [ 29 , 30 ]. Overall, further studies are needed to establish whether patients with and without reduced cognitive function, and prolonged use of CNSDs are at risk of increased likelihood of death.…”
Section: Introductionmentioning
confidence: 99%